High-flux water desalination with interfacial salt sieving effect in nanoporous carbon composite membranes - Chen, Wei; Chen, Shuyu; Liang, Tengfei; Zhang, Qiang; Fan, Zhongli; Yin, Hang; Huang, Kuo-Wei; Zhang, Xixiang; Lai, Zhiping; Sheng, Ping (Nature nanotechnology, 2018)
Freshwater flux and energy consumption are two important benchmarks for the membrane desalination process. Here, we show that nanoporous carbon composite membranes, which comprise a layer of porous carbon fibre structures grown on a porous ceramic substrate, can exhibit 100% desalination and a freshwater flux that is 3–20 times higher than existing polymeric membranes. Thermal accounting experiments demonstrated that the carbon composite membrane saved over 80% of the latent heat consumption. Theoretical calculations combined with molecular dynamics simulations revealed the unique microscopic process occurring in the membrane. When the salt solution is stopped at the openings to the nanoscale porous channels and forms a meniscus, the vapour can rapidly transport across the nanoscale gap to condense on the permeate side. This process is driven by the chemical potential gradient and aided by the unique smoothness of the carbon surface. The high thermal conductivity of the carbon composite membrane ensures that most of the latent heat is recovered. Nanoporous carbon composite membranes exhibit 100% salt rejection and high water flux due to the interfacial sieving effect and the fast transport of vapour in carbon pores, respectively.